MAKNA AUTOIMUN BAGI PEREMPUAN SEBAGAI KONTEN KREATOR PADA TIKTOK @CANTIK2AUTOIMUN - Rahman, Mufti Fauzi; Dahliah, Dedeh (TECHNO-SOCIO EKONOMIKA, 2024)
This study aims to analyze how the TikTok content creator @cantik2autoimun represents the experiences of women living with autoimmune diseases and how the meaning of this illness is shaped through social interactions on the platform. A qualitative approach with a phenomenological method is employed, involving four informants selected for their active participation in creating autoimmune-related content on TikTok. Data were collected through in-depth interviews and document and content analysis. Data validity was ensured through source triangulation and peer discussions, helping to maintain consistency in data interpretation. The results show that, through TikTok, content creators highlight themes of self-acceptance, education on autoimmune diseases, and the social stigma faced by individuals with such conditions. Interactions with followers reveal shifts in public understanding of autoimmune conditions, despite the risks associated with self-diagnosis. This research offers insights into the role of social media in shaping the meaning of chronic illness and providing emotional support and education for the public.